STUDI BERBAGAI JENIS BAHAN PENGEMBANG TERHADAP REABSORPSI TEKWAN KERING IKAN GABUS - H.K, Rio Danar; Dasir, Dasir (Universitas Muhammadiyah Palembang, 2017)
This study aims to determine the use of various types of developer materials to snakehead fish dry tekwan reabsorption. This study was conducted in the laboratory of the Agriculture Faculty, University of Muhammadiyah and Industrial Research and Standards, Palembang in June 2016 to August 2016. Research on the topic